Arya a socio-cultural heritage center for Sariaya, Quezon - De Leon, Jan Kamilla O.; Sarthou, Armin Jr. B. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Sariaya is a humble and sleeping town in the Quezon Province. Most people, even locals, may not even know that Sariaya is dubbed as the Heritage Town of Quezon, the Art Deco Capital of Southern Luzon, and even as the Vigan of the South. With the focus being on its beach resorts and with the popularity of other Quezon Towns, the culture and heritage at the town at the heart of Sariaya is being disregarded and forgotten. Withe ARYA Sariaya as my guiding principle, the approach of rural tourism was usd to establish the agenda and achieve the design mission which is to preserve, to showcase and to foreward the town's heritage and culture. To achieve this the project was designed (1) to enhance and facilitate cohesion, involvement and participation, (2) to serve a space that could work for multiple purposes such as meetings, dances, activities and many others gatherings, (3) to serve as a place for community use and enjoyment, and (4) to become a place that is open and available for everyone. Adaptive reuse would be employed on a Heritage Mansion. From being residential, it would be converted into a restaurant/cafe/events space. With this, its spirit of welcoming guests and hosting parties and gatherings would be kept alive. It would also bring back to life the spirit of old public establishments in Sariaya that are no longer there such as the Joseph's Theater, Sariling Atin and Kapatiran.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Arts facilities -- Quezon Province -- Philippines